Cardiac arrest after pulmonary aspiration in hospitalised patients: a national observational study - Andreas Claesson; Mattias Ringh; Per Nordberg; Johan Herlitz; Araz Rawshani; Therese Djärv; Malin Albert (BMJ Open)
Objective To study characteristics and outcomes among patients with in-hospital cardiac arrest (IHCA) due to pulmonary aspiration.Design A retrospective observational study based on data from the Swedish Registry of Cardiopulmonary Resuscitation (SRCR).Setting The SRCR is a nationwide quality registry that covers 96% of all Swedish hospitals. Participating hospitals vary in size from secondary hospitals to university hospitals.Participants The study included patients registered in the SRCR in the period 2008 to 2017. We compared patients with IHCA caused by pulmonary aspiration (n=127), to those with IHCA caused by respiratory failure of other causes (n=2197).Primary and secondary outcome measures Primary outcome was 30-day survival. Secondary outcome was sustained return of spontaneous circulation (ROSC) defined as ROSC at the scene and admitted alive to the intensive care unit.Results In the aspiration group 80% of IHCA occurred on general wards, as compared with 63.6% in the respiratory failure group (p<0.001). Patients in the aspiration group were less likely to be monitored at the time of the arrest (18.5% vs 38%, p<0.001) and had a significantly lower rate of sustained ROSC (36.5% vs 51.6%, p=0.001). The unadjusted 30-day survival rate compared with the respiratory failure group was 7.9% versus 18.0%, p=0.024. In a propensity score analysis (including variables; year, age, gender, location of arrest, initial heart rhythm, ECG monitoring, witnessed collapse and a previous medical history of; cancer, myocardial infarction or heart failure) the OR for 30-day survival was 0.46 (95% CI 0.19 to 0.94).Conclusions In-hospital cardiac arrest preceded by pulmonary aspiration occurred more often on general wards among unmonitored patients. These patients had a lower 30-day survival rate compared with IHCA caused by respiratory failure of other causes.